2022
DOI: 10.1002/admi.202200498
|View full text |Cite
|
Sign up to set email alerts
|

Structural Defects Improve the Memristive Characteristics of Epitaxial La0.8Sr0.2MnO3‐Based Devices

Abstract: of Moore's law in mind, industry and academia moved the focus to new approaches and alternative materials. In this scenario, resistive random access memories (RRAM) are considered promising candidates for the next generation of nonvolatile memories, due to their fast writing speed, high storage density, high endurance, long retention times, and low energy consumption. [1] By applying an electric stimulus, these devices exhibit a reversible change of resistance retained under zero-field conditions, and hence hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…In our previous work, we showed that the LSM20/LAO-based devices show reproducible and multilevel resistive switching, that was largely improved by the presence of dislocations. [3] The LSM20 devices required larger operating voltage and the HRS/ LRS window was smaller, typically between 1.3 and 5 for V amp = 4 to 20 V. In the present work, we exploited the easy formation of oxygen vacancies in LSM50 to obtain larger operating windows at smaller voltages, i.e., 2.1 to 184 for V amp = 4 to 12 V. These results clearly show that it is possible to improve and optimize the memristive properties similar devices by modifying the Sr substitution of the manganite, leading to changes in ionic and electronic conductivity of the material.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous work, we showed that the LSM20/LAO-based devices show reproducible and multilevel resistive switching, that was largely improved by the presence of dislocations. [3] The LSM20 devices required larger operating voltage and the HRS/ LRS window was smaller, typically between 1.3 and 5 for V amp = 4 to 20 V. In the present work, we exploited the easy formation of oxygen vacancies in LSM50 to obtain larger operating windows at smaller voltages, i.e., 2.1 to 184 for V amp = 4 to 12 V. These results clearly show that it is possible to improve and optimize the memristive properties similar devices by modifying the Sr substitution of the manganite, leading to changes in ionic and electronic conductivity of the material.…”
Section: Discussionmentioning
confidence: 99%
“…[15,46] The metal-organic precursors, La(thd) 3 , Sr(thd) 2 -tetraglyme, and Mn(thd) 3 , [thd = 2,2,6,6,-tetramethyl-3,5-heptanedionato] were purchased from Strem Chemicals and were dissolved in m-xylene from Alfa Aesar. As an extension to the composition preliminary study, [3] the cationic concentration in the solution was optimized to grow films with 50% strontium substitution and [(La+Sr)/Mn] ratio close to 1. The total concentration of the solution was 22.5 mM, with [(La+Sr)/Mn] precursor ratio of 2.3 and [Sr/(La+Sr)] precursor ratio of 0.8.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, we focus on the impact of B-site deficiency on oxygen mass transport properties (i.e. oxygen diffusivity and surface exchange coefficient) of La 0.8 Sr 0.2 Mn y O 3±δ (LSM y ), a material relevant for diverse applications, such as solid oxide fuel cells and electrolyzers, supercapacitors [20] and resistive switching [21]. The defect chemistry of bulk LSM is strongly dominated by cation vacancies, which give rise to the oxygen hyper-stoichiometry observed in oxidizing conditions [22,23].…”
Section: Introductionmentioning
confidence: 99%